MiR‐148a‐3p silences the CANX/MHC‐I pathway and impairs CD8+ T cell‐mediated immune attack in colorectal cancer. Issue 8 (29th July 2021) - Zheng, Jinxiu; Yang, Ting; Gao, Shuhua; Cheng, Minrong; Shao, Ying; Xi, Yanfeng; Guo, Linzhi; Zhang, Dong; Gao, Wei; Zhang, Guozhen; Yang, Lijun; Yang, Tao
Abstract: Nonresponse, or acquired resistance to immune checkpoint inhibitors in colorectal cancer (CRC) highlight the importance of finding potential tolerance mechanisms. Low expression of major histocompatibility complex, class I (MHC‐I) on the cell surface of the tumor is one of the main mechanisms of tumor escape from T‐cell recognition and destruction. In this study, we demonstrated that a high level of calnexin (CANX) in the tumors is positively correlated with the overall survival in colorectal cancer patients. CANX is a chaperone protein involved in the folding and assembly of MHC‐I molecules. Using miRNA target prediction databases and luciferase assays, we identified miR‐148a‐3p as a potential regulator of CANX. Inhibition of miR‐148a‐3p restores surface levels of MHC‐I and significantly enhanced the effects of CD8 + T‐cell‐mediated immune attack in vitro and in vivo by promoting CANX expression. These results reveal that miR‐148a‐3p can function as a tumor promotor in CRC by targeting the CANX/MHC‐I axis, which provides a rationale for immunotherapy through targeting the miR‐148a‐3p/CANX/MHC‐I pathway in patients with CRC.